If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3n + 6 = -1(3n + -7) + -5 Reorder the terms: 6 + -3n = -1(3n + -7) + -5 Reorder the terms: 6 + -3n = -1(-7 + 3n) + -5 6 + -3n = (-7 * -1 + 3n * -1) + -5 6 + -3n = (7 + -3n) + -5 Reorder the terms: 6 + -3n = 7 + -5 + -3n Combine like terms: 7 + -5 = 2 6 + -3n = 2 + -3n Add '3n' to each side of the equation. 6 + -3n + 3n = 2 + -3n + 3n Combine like terms: -3n + 3n = 0 6 + 0 = 2 + -3n + 3n 6 = 2 + -3n + 3n Combine like terms: -3n + 3n = 0 6 = 2 + 0 6 = 2 Solving 6 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| Log*2x-log*11=1 | | 2(-5n-2)=24+4n | | -8(1+m)-7=-4(-5+2m) | | y=ln(12x)-12x+16 | | 11.8=k-8 | | 14.60=5+0.8x | | -120x=-150 | | 7x-(5-2x)=13 | | 12x-4x+7-3x= | | 3x+22=2(3x+8) | | 4(-5+2n)=-23+8n | | 6x+2=-8+7x | | -120x=-150x | | 18-6x=4x^2 | | -11+2x=x-3+2x | | 4t=t+18 | | 4(4x-4)=17 | | -120x=-160x | | -16+6p=p+8+p | | x+11=6x+1 | | (2x+1)-(3x+4)= | | 5x+12+23+3y-10+2x-9=360 | | -8(5y-4)+10y-12= | | Y=4000(.65)x | | 5n+3=7n-3-8 | | Y=36(1.09)x | | 5c-4-10c+1=2 | | 3x-1+1=0 | | 6x+14+8x=2x+3 | | 4a+6-3a-7= | | p-9=p-1 | | K^5+4k-32k^3=0 |